PECULIARITIES OF THE EU SINGLE ENVIRONMENTAL MARKET FORMATION AND DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The development of the environmental market is a global trend, which is particularly dynamic in the EU. European countries have shown a significant role for the environmental goods and services sector in ensuring their economic growth. Today, in the area of ​​integration, this sector is dynamically developing as environmental demands of consumers for the products and environmental quality in general have increased. The processes of investing in energy efficiency improvement, development and implementation of eco-friendly technologies and waste management have significantly intensified. Therefore, priority is given to the development of EU single environmental market.The purpose of the article is to study the features of forming a single environmental market in the countries of the European Union and to identify current trends of it development.The authors determine that the environmental market and the market of ecological goods and services are practically identical categories, and the eco-industry is a component and basis of formation and development. The article describes the basic prerequisites for the creation of EU single environmental market, among which fiscal restrictions and prohibitions on the manufacture of products containing harmful substances are highlighted; formation of certification and eco-labeling programs by the European Commission; increasing demand for environmentally friendly products and services, driven by a worldwide trend towards environmental conservation and health.The structure of the EU single environmental market sectors is analyzed. The article emphasizes that one of the defining features of the development of the EU organic produce market is the constant increase in demand and price increases of 20-50% compared to the traditional market.The EU single environmental market is one of the most developed in the world. The rapid growth of its development is expected, which in turn will make the ecological industry promising in the future. The main trends in the development of the EU single environmental market are: an increase in the production of organic products and the provision of services according to market needs; increase in the number of employees in the field of eco-industry. Increasing public awareness of how lifestyle and consumer choices affect the environment, which in turn has led to increased demand for eco-friendly products and services.
Keywords: single ecological market, eco-industry, organic products, environmental services, European Union